The Impacts Of Total Population, Unemployment Rate And Urban Population Rate Towards The Total Municipal Waste Disposal In The Three Scandinavian Countries : A Panel Data Analysis - Adrianne Favianne, Alex (Universiti Malaysia Sarawak (UNIMAS), 2020)
Environment sustainability plays a vital role as it indirectly affects the well-being of a country. There are many aspects of environment issues that needs to be focused on and this study chooses to highlight the municipal solid waste topic. By applying a panel data analysis, this paper is determined to examine the impact of economic variables towards the total municipal waste disposal in Denmark, Norway and Sweden. Various economic variables have been proven to affect the municipal waste disposal in a country. ln this study, total population, unemployment rate and urban population rate from 2003 until 2017 will be used to analyze its influence on the total municipal waste disposal. Methods adopted are the panel unit root tests, panel cointegration tests FMOLS as well as panel Granger causality test. It is found that all variables are significant in this study and affects the total municipal waste disposal in short run of the Scandinavian countries. However, the study finds that unemployment rate 1s insignificant to the total of municipal waste disposal in the long run.